Preliminary Groundwater Assessment using Electrical Method at Quaternary Deposits Area - Hazreek, Z.A.M; Raqib, A.G.A.; Aziman, M.; Azhar, A.T.S.; Khaidir, A.T.M.; Fairus, Y.M.; Rosli, S.; Mohd Fakhrurrazi, Ishak; Izzaty, R.A. (IOP Publishing Ltd, 2017)
Alternative water sources using groundwater has increasingly demand in recent years. In the past, proper and systematic study of groundwater potential was varies due to several constraints. Conventionally, tube well point was drilled based on subjective judgment of several parties which may lead to the uncertainties of the project success. Hence, this study performed an electrical method to investigate the groundwater potential at quaternary deposits area particularly using resistivity and induced polarization technique. Electrical method was performed using ABEM SAS4000 equipment based on pole dipole array and 2.5 m electrode spacing. Resistivity raw data was analyzed using RES2DINV software. It was found that groundwater was able to be detected based on resistivity and chargeability values which varied at 10 – 100 Ωm and 0 – 1 ms respectively. Moreover, suitable location of tube well was able to be proposed which located at 80 m from the first survey electrode in west direction. Verification of both electrical results with established references has shown some good agreement thus able to convince the result reliability. Hence, the establishment of electrical method in preliminary groundwater assessment was able to assist several parties in term groundwater prospective at study area which efficient in term of cost, time, data coverage and sustainability.